The Analysis of Guest Satisfaction Level Towards the Teaching Factory at De Balen Soultan Hotel - Gumilar, Gugung; Hali, Muhammad Sultan; Sulartiningrum, Sri (Institut Pariwisata Trisakti, 2025)
Abstract This study aims to analyze the effect of implementing the Teaching Factory system on guest satisfaction at De Balen Soultan Hotel. The method used is a quantitative approach with descriptive and causal designs. The sample consists of 100 respondents selected using purposive sampling technique. Data were collected through questionnaires using a Likert scale to measure the dimensions in the SERVQUAL model, which include tangibles, reliability, responsiveness, assurance, and empathy. The data were analyzed using descriptive statistics and simple linear regression techniques. The results of the study show that guest satisfaction has a significant effect on the implementation of the teaching factory. The dimensions of tangibles, reliability, responsiveness, assurance, and empathy each have a significant impact on guest satisfaction. The discussion reveals that the implementation of the teaching factory improves students' practical skills, which directly affects the quality of service at the hotel. The conclusion of this study is that the implementation of the Teaching Factory at the hotel has a positive impact on guest satisfaction. Recommendations for De Balen Soultan Hotel include continuously improving service quality by paying attention to guest feedback, while for students, it is suggested to be more active in practical training to better prepare for the workforce. Keywors: teaching factory, guest satisfaction, SERVQUAL, hospitality